Sublethal effects of a mass mortality agent: pathogen-mediated plasticity of growth and development in a widespread North American amphibian - Billet, Logan S.; Skelly, David K. (Frontiers in Amphibian and Reptile Science, 2025)
Amphibians exhibit diverse responses to environmental challenges, but their responses to infection risk remain poorly understood. This study investigates how the presence of ranavirus, a deadly viral pathogen, affects growth, development, and resource allocation in wood frog (Rana sylvatica [Lithobates sylvaticus]) tadpoles. Using three years of pond survey data from a wood frog metapopulation in northeastern Connecticut, USA, we compared tadpole physiological rates across three scenarios: ranavirus-free ponds, ponds with sustained ranavirus infection, and ponds experiencing ranavirus die-offs. In ranavirus-positive ponds, tadpoles exhibited increased growth and resource allocation early in their development. These differences waned following die-off events in some ponds but persisted where widescale infection did not lead to die-off. This study provides evidence that an important disease agent appears to induce growth and developmental responses in its host that may help tadpoles survive severe infection by providing a buffer against the associated energetic demands. Alternative hypotheses, such as size-biased mortality, should be evaluated in experiments aimed at evaluating underlying mechanisms.